Relationships, Layoffs, and Organizational Resilience: Airline Industry Responses to September 11 - Jody Hoffer Gittell; Kim Cameron; Sandy Lim; Victor Rivas (Economics and Econometrics Research Institute (EERI), 2005)
The terrorist attacks of September 11th, 2001 affected the U.S. airline industry more than almost any other industry. Certain of these companies emerged successful, however, and demonstrated remarkable resilience while others languished. This investigation identifies the reasons why some airline companies recovered successfully after the attacks while others struggled. Evidence is provided that layoffs after the crisis, while intended to foster recovery, instead inhibited recovery throughout the four years after the crisis. But layoffs after the crisis were strongly correlated with the lack of financial reserves and the lack of a viable business model prior to the crisis. Digging deeper, we find that having a viable business model itself depended on the extent to which positive employee relationships had been achieved and maintained over the long term. One implication of our findings is that layoffs, while reducing costs in the short term, may also undermine the positive relationships that are critical for achieving lasting recovery.
Keywords: L93; 330; Relationships; layoffs; organizational resilience; terrorist attacks; aviation